PENGARUH BRAND IMAGE DAN KUALITAS PRODUK PENGARUH TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI KOPI NUR - Zefri Efdison,; Anggil Nopra Lova,; Deky Hamdani, (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2023)
This study aims to determine the effect of price and product quality on consumer purchase decision of Nur Cofee. The sample from this study was 100 respondents. Data were collected with questionnaires that had been tested for validity and reliability. The data analysis techniques used are analysis, descriptive, multiple regression, coefficient of determination and hypothesis testing using the t test and the f test. The results showed that there was a significant influence between price on consumer purchase decision of citra alam inn. There is a significant influence between the product quality on consumer purchase decision of Nur Cofee. There is a significant influence between facilities, quality of service and experience on consumer purchase decision of citra alam lodging 2 simultaneously or together